2020
DOI: 10.1212/nxi.0000000000000852
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput investigation of molecular and cellular biomarkers in NMOSD

Abstract: ObjectiveTo identify candidate biomarkers associated with neuromyelitis optica spectrum disorder (NMOSD) using high-throughput technologies that broadly assay the concentrations of serum analytes and frequencies of immune cell subsets.MethodsSera, peripheral blood mononuclear cells (PBMCs), and matched clinical data from participants with NMOSD and healthy controls (HCs) were obtained from the Collaborative International Research in Clinical and Longitudinal Experience Study NMOSD biorepository. Flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
4
15
0
Order By: Relevance
“…A marked increase of the T cell and B cell counts was observed after the therapy ( Table 2 ), with a reduced proportion of the activated T (CD3+HLA-DR+) and Ts cells (CD3+CD8+HLA-DR+), implying a possibly improved immune system, which could be a downstream effect after the clearance of the pro-inflammatory mediators. In contrast, the percent and number of NK cells had a pronounced drop, which was also noted by previous studies as a potential biomarker candidate for acute-phase NMOSD ( 19 , 20 ), although the underlying cause has been still unclear. A significantly increased level of Tregs (CD3+CD4+CD25+CD127low+) after immunoadsorption treatment in a previous study ( 21 ) was not found in our case.…”
Section: Discussionsupporting
confidence: 72%
“…A marked increase of the T cell and B cell counts was observed after the therapy ( Table 2 ), with a reduced proportion of the activated T (CD3+HLA-DR+) and Ts cells (CD3+CD8+HLA-DR+), implying a possibly improved immune system, which could be a downstream effect after the clearance of the pro-inflammatory mediators. In contrast, the percent and number of NK cells had a pronounced drop, which was also noted by previous studies as a potential biomarker candidate for acute-phase NMOSD ( 19 , 20 ), although the underlying cause has been still unclear. A significantly increased level of Tregs (CD3+CD4+CD25+CD127low+) after immunoadsorption treatment in a previous study ( 21 ) was not found in our case.…”
Section: Discussionsupporting
confidence: 72%
“…Besides, in our study, the counts of WBCs, neutrophils, and monocytes were elevated, suggesting a systemically activated immune system triggered by the severe episodes or prodromal infections in patients with MOGAD, especially in those presenting with acute disseminated encephalomyelitis. A significantly reduced NK-cell level seemed specific for NMOSD when compared to MS and MOGAD, which was also observed by previous studies [28,29]. Nevertheless, the underlying cause of this finding has been still an enigma due to a paucity of T cells and NK cells in or around the NMO lesions [21], although NK cells may participate in the development of NMOSD by antibodydependent cellular cytotoxicity [30].…”
Section: Discussionsupporting
confidence: 69%
“…A significantly reduced NK-cell level seemed specific for NMOSD when compared to MS and MOGAD, which was also observed by previous studies [28, 29]. Nevertheless, the underlying cause of this finding has been still an enigma due to a paucity of T cells and NK cells in or around the NMO lesions [21], although NK cells may participate in the development of NMOSD by antibody-dependent cellular cytotoxicity [30].…”
Section: Discussionsupporting
confidence: 69%
“…While major advances in the knowledge of NMOSD pathophysiology have led to investigating the efficacy of targeted treatments in phase III clinical trials, further elucidation of the immunopathogenesis of AQP4+ NMOSD may lead to novel treatment approaches. Besides IL-6, CCL22 and CCL3, CD16 + CD56 + NK cells and CX3CL1 have been identified as potential novel biomarker candidates [ 46 ]. Besides the assessment of the frequency of various immune cell types [ 46 ], their functional characteristics need further exploration.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…Besides IL-6, CCL22 and CCL3, CD16 + CD56 + NK cells and CX3CL1 have been identified as potential novel biomarker candidates [ 46 ]. Besides the assessment of the frequency of various immune cell types [ 46 ], their functional characteristics need further exploration. For instance, the role and function of antigen-presenting cells, such as dendritic cells, have not been clarified so far.…”
Section: Immunopathogenesismentioning
confidence: 99%